Post-termination Effects of Cover Crop Monocultures and Mixtures on Soil Inorganic Nitrogen and Microbial Communities on Two Organic Farms in Illinois - Lucadamo, Eleanor E.; Holmes, Ashley A.; Wortman, Sam E.; Yannarell, Anthony C. (Frontiers in Soil Science, 2022)
Cover crops can continue to affect agricultural systems even after they have been terminated by influencing nitrogen dynamics and by altering soil microbial communities. These post-termination effects can influence soil fertility, weed pressure, and the dynamics of potential plant pathogens in the narrow window of time between cover crop termination and cash crop emergence. We evaluated the post-termination effects of 12 different spring-sown cover crop mixtures and monocultures on soil nitrogen and microbial communities on two different organic farms in Central Illinois (on Lawson silt loam soil) and Northern Illinois (on Virgil silt loam soil). In comparison to control plots with no cover crops, all cover crop treatments significantly reduced soil nitrate levels but increased the potentially mineralizable nitrogen pool following termination. Nitrate levels of cover crop plots approached those of controls after 2 and 4 weeks, respectively, but potentially mineralizable nitrogen levels in cover plots remained elevated for at least 4 weeks following termination. Monocultures of Brassica cover crops showed the greatest decrease in soil nitrate, while Brassicas and unplanted control plots containing high biomass of weeds showed the greatest increase in potentially mineralizable nitrogen in comparison to plant-free control plots. In contrast to their effect on soil nitrogen, cover crops had very limited impact on the composition of soil microbial communities. Overall microbial community composition varied across sites and years, and only soil fungi significantly responded to cover cropping treatments. Nevertheless, we found that some highly correlated groups of soil microbes showed significant responses to soil nitrate and to high plant biomass. Key members of these correlated groups included ammonia-oxidizing organisms and saprotrophic fungi. Our results suggest that cover crops may reduce the potential for springtime nitrogen leaching losses by retaining nitrogen in the soil organic pool, and they may also have impacts on the soil microbial community that are particularly relevant for nitrogen cycling and decomposition of plant residues.